Mutu Pendidikan Tinggi Islam: Pengembangan Etika Islam dan Peningkatan Kompetensi Akademik dalam Pengembangan Profesional dan Keterlibatan Dosen Perguruan Tinggi Islam Indonesia - Alfarizi, Muhammad; Megawati, Suci (Balai Diklat Keagamaan Surabaya, 2024)
The development of higher education, especially Islamic Religious Universities (PTKI), focuses on innovation in teaching, learning, and the ethics of lecturers as role models. PTKI plays an important role in shaping an excellent generation through the integration of knowledge and Islamic values. This study aims to explore the contribution of academic competence enhancement programs and Islamic educators' ethics development to the professional development of PTKI lecturers, as well as their impact on academic work engagement. The research uses an exploratory quantitative approach with a cross-sectional design to examine PTKI lecturers' professional development. Data were collected through open-ended questionnaire surveys of 150 respondents selected via purposive sampling. Data analysis was conducted using the PLS-SEM technique to evaluate the validity of the structural model and the relationships between latent variables and their indicators. The findings show that academic competence enhancement programs and Islamic educators' ethics development have a significant positive impact on lecturers' professional development. Professional development directly influences and mediates academic work engagement. Lecturers who continuously develop their competence and ethics tend to be more engaged in academic tasks, highly committed, and capable of creating dynamic and collaborative learning environments. This study encourages PTKI to design ongoing training programs tailored to lecturers' needs and promote inter-campus synergy through research collaboration.